Functional Properties of Enzymatic Hydrolysate and Peptide Fractions from Perilla Seed Meal Protein - Bo Yeon Park; Kyung Young Yoon (Polish Journal of Food and Nutrition Sciences)
The present study aimed to decompose perilla seed meal (PSM) proteins via enzymatic degradation and to evaluate the functional properties of the resulting enzymatic hydrolysate and peptide fractions for utilization of PSM, a by-product in the production of perilla seed oil. PSM protein hydrolysates were fractionated based on molecular weight using an ultrafiltration system, and the physical properties required to utilize the hydrolysate and peptide fractions as functional food components were determined. The enzymatic hydrolysate and peptide fractions showed higher solubility, oil absorption capacity, and emulsifying and foaming properties than protein isolates. In particular, peptide fractions below the 5 kDa showed high solubility, emulsifying activity, and foaming capacity. Therefore, these peptide fractions are ideal as functional raw materials and substitutes that can be used to improve the quality of various processed food products and protein supplements.